One-Step Purification of Microbially Produced Hydrophobic Terpenes via Process Chromatography - Grozdev, Ljubomir; Kaiser, Johann; Berensmeier, Sonja (Frontiers in Bioengineering and Biotechnology, 2019)
Novel and existing terpenes are already being produced by genetically modified microorganisms, leading to new process challenges for the isolation and purification of these terpenes. Here, eight different chromatographic resins were characterized for the packed bed adsorption of the model terpene β-caryophyllene, showing their applicability on an Escherichia coli fermentation mixture. The polystyrenic Rensa® RP (Ø 50 µm) shows the highest affinity, with a maximum capacity of > 100 g L-1 and the best efficiency, with a height equivalent of a theoretical plate (HETP) of 0.022 cm. With this material, an optimized adsorption-based purification of β-caryophyllene from a fermentation mixture was developed, with the green solvent ethanol for desorption. A final yield of > 80% and a purity of > 99% were reached after only one process step with a total productivity of 0.83 g h-1 L-1. The product solution was loaded with a volume ratio (feed to column) of > 500, and the adapted gradient elution yielded a 40 times higher concentration of β-caryophyllene. The adsorption-based chromatography represents therefore a serious alternative to the liquid-liquid extraction and achieves desired purities without the utilization of hazardous solvents.